A Comparison of the α2/3/5 Selective Positive Allosteric Modulators L-838, 417 and TPA023 in Preclinical Models of Inflammatory and Neuropathic Pain. (28th November 2011) - Nickolls, Sarah; Mace, Hannah; Fish, Rebecca; Edye, Michelle; Gurrell, Rachel; Ivarsson, Magnus; Pitcher, Tom; Tanimoto-Mori, Sachi; Richardson, Denise; Sweatman, Catherine; Nicholson, Janet; Ward, Cameron; et al.
Abstract : GABA A receptors containing α 2/3 subunits are current targets in the battle to develop new pain medications, as they are expressed in the spinal cord where increasing inhibitory drive should result in analgesia. However, this approach is prone to a range of side effects including sedation, cognitive impairment, and abuse as a consequence of the widespread influence of GABA. The ability to make subtype selective low-efficacy benzodiazepine compounds, which potentiate the action of GABA at specific α subunits, has the potential to reduce this side effect profile. In this study, we have investigated the effects of the medium-efficacy positive allosteric modulator (PAM) L-838, 417 and the low-efficacy PAM TPA023 in a number of preclinical inflammatory and neuropathic pain models. We conclude that either the higher level of efficacy at α 2/3 or efficacy at α 5 is required for compounds to have a significant analgesic effect in a range of models, and, therefore, although the side-effect profile of compounds can be reduced compared to typical benzodiazepines, it is unlikely that it can be completely eliminated.